Produksi dan stabilisasi desaturase dari Absidia corymbifera Production and stabilization of desaturases from Absidia corymbifera - . TRI-PANJI; . SUHARYANTO; A W PAULUS; K SYAMSU; A M FAUZI (INDONESIAN OIL PALM RESEARCH INSTITUTE, 2002)
SummaryDesaturases are enzymes which catalyze desaturation process on carbon chain of fatty acids into unsaturated fatty acids useful for healthy oil. Desaturases could be produced from Absidia corymbifera and applied for increasing unsaturation level and crude palm oil (CPO) quality. Desaturases have been known as very unstable enzymes. The objective this research was to determine carbon sources and culture time for optimum desaturase production, fatty acid composition resulted from desaturase bioconversion, and methods for stabilization of desaturase from A. corymbifera. Results showed that desaturases from A. corymbifera are intracellular enzymes that reached the highest activity in Serrano-Careon medium with C sources of a mixture of sucrose and paraffin (0.14 U/mL) and C sources of molasses (0.11 U/mL) incubated for 76 and 120 hours respectively. Activity of ∆6 and ∆12 desaturases have been detected in culture filtrate of A. corymbifera. Activiy of ∆12 desaturase was confirmed by increasing of linoleic acid in CPO incubated with culture filtrate and biomass extract, while activity of ∆6 was detected by its conversion as much as 66.48 % linoleic acid into gamma linolenic acid (GLA) that having high economic value. Precipitation of culture filtrate and lipid extraction of biomass were unable to stabilize desaturases. Desaturase degradation rate could be inhibited by isolation and washing of microsome fraction using high salt buffer. This method could stabilize desaturases 70-80% from initial activity at storage temperature 25o C and 50 o C for 6 hours. RingkasanDesaturase merupakan enzim yang berperan dalam proses desaturasi rantai karbon asam lemak menjadi asam lemak tak jenuh yang banyak manfaatnya bagi kesehatan. Desaturase dapat dihasilkan dari Absidia corymbifera dan diamplifikasikan untuk peningkatan ketidakjenuhan dan kualitas minyak sawit mentah (CPO). Enzim desaturase dikenal sangat tidak stabil. Penelitian bertujuan menetapkan sumber karbon dan waktu kultur yang memberikan aktivitas desaturase tertinggi, komposisi asam lemak hasil konversi desaturase dan cara menstabilkan desaturase dari A. corymbifera. Hasil penelitian menunjukkan bahwa desaturase dari A. corymbifera merupakan enzim intraselular yang mencapai aktivitas tertinggi pada medium Serrano-Careon dengan sumber karbon campuran sukrosa dan parafin (0,14 U/mL) dan sumber karbon molases (0,11 U/mL) masingmasing pada inkubasi selama 76 dan 120 jam. Aktivitas ∆6 dan ∆12 desaturase terdeteksi pada cairan fermentasi A. corymbifera. Aktivitas ∆12 desaturase terdeteksi dari peningkatan persentase asam linoleat pada CPO yang telah diinkubasi dengan cairan fermentasi atau ekstrak biomassa, sedangkan aktivitas ∆6 desaturase terdeteksi dari dikonversinya sebesar 66,48% asam linoleat menjadi asam gamma linolenat (GLA) yang memiliki potensi nilai ekonomis lebih tinggi. Pengendapan filtrat kultur fermentasi dan ekstraksi lipida biomassa tidak mampu menstabilkan desaturase. Laju degradasi desaturase dapat dihambat dengan cara isolasi dan pencucian fraksi mikrosom dengan bufer garam. Cara tersebut dapat mempertahankan aktivitas desaturase 70–80% pada penyimpanan suhu 25o C dan 50o C selama enam jam.